FINANCIAL LITERACY VS BUY NOW PAY LATER: APAKAH GAYA HIDUP KONSUMTIF GEN Z MEMPERKUAT ATAU MEMPERLEMAH? - Khoirunisa, Rizqi; Mustofa, Ahmad; Setyawan, Bimo; Kurnia, Lely Indah (Media Mahardhika, 2025)
This study aims to analyze the influence of financial literacy on the use of Buy Now Pay Later (BNPL) services among Generation Z and examine the moderating role of a consumptive lifestyle in this relationship. The research employs a quantitative approach using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Data were collected from 110 Generation Z respondents in Lumajang Regency who had used BNPL services through an online questionnaire. Data analysis was conducted using SmartPLS 4.0 to test the relationships between variables. The results indicate that financial literacy has a significant negative effect on BNPL usage, and a consumptive lifestyle weakens the negative impact of financial literacy on BNPL usage. The implications of these findings suggest the need for financial education strategies that focus more on controlling consumptive behavior, as well as stricter regulations on BNPL services to prevent increased debt among Generation Z.